(untitled) (Baghdad Science Journal, 2019)
Na+/K+-ATPase is a prevalent enzyme that maintains the Na+ and K+ gradients across the cell membrane by transporting three Na+ out and two K+ into the cell, the aim of this study is to provide detailed mechanistic insights, potentially with important effects on physiological regulation of active Na and K transport in tissues of Aerobic Thyroid Patient. Thyroid tissues were obtained from a 35 year old patients, the operation was carried out at the Al-Hadi Specialist Hospital in Samarra city, the sample was stored at -20ºC until used. The purification protocol included Salt Precipitation, Ion Exchange Chromatography, Gel Filtration and Electrophoresis, a spectrophotometric method was used to determine the enzyme activity. kinetic parameters was also obtained for the enzyme. Partial purification of Na+/K+-ATPase revealed two isoenzymes (I ,II). The purity of separated isoenzymes were proved by SDS-PAGE electrophoresis. The kinetic characteristics of Na+/K+-ATPase showed that optimum substrate concentration about 1.5mM, Km 1.052mM, and Vmax 6.062, optimum temperature was 37 ºC, optimum pH 7.4 and optimum time in 25 min. Na+/K+-ATPase purified from Thyroid tissue has distinct kinetic characteristic that reflects the importance of intracellular regulation of specific Na+/K+-ATPase pump which gives cells the ability to precisely coordinate to their physiological requirements .